Effectiveness of ginger aromatherapy towards nausea and vomiting on first trimester pregnant women at BPM (private practice midwives) Ni Wayan Suri in Denpasar City - Dewianti, Ni Made; Witari, Ni Nyoman Deni (International Journal of Research in Medical Sciences, 2019)
Background: Nausea and vomiting in pregnancy are called morning sickness, which is experienced by around 70-80% of pregnant women, is a phenomenon that often occurs at 5-12weeks of gestation. Since long time ago, ginger has been known as a plant with a million of medicinal properties. Non-pharmacological intervention measures by giving ginger aromatherapy is part of the comfort intervention which aimed to provide physical comfort to pregnant women. Methods: The design of this study was pre-experimental (Quasi experiment design) with one group pretest-posttest design on the group that was given ginger aromatherapy. The population in this study was pregnant women who made antenatal visits at Private Practice Midwives (hereafter BPM) Ni Wayan Suri in Denpasar City in 2018 with purposive sampling technique. The samples in this study were first trimester pregnant women who experienced nausea and vomiting in BPM Ni Wayan Suri in Denpasar City and met the inclusion criteria. The number of samples in this study was 30 people. Data were analyzed through t-test to compare the results of the pretest and posttest. Results: The average nausea and vomiting of pregnant women in the first trimester before receiving ginger aroma therapy was 8.1. The average nausea and vomiting of pregnant women in the first trimester upon receiving the aroma of ginger therapy was 6 with a p value of 0.00 which means that there was an effect of ginger aromatherapy on nausea and vomiting of pregnant women in first trimester in Private Practice Midwives BPM Ni Wayan Suri in Denpasar City. Conclusions: There is an effect of ginger aromatherapy on nausea and vomiting of pregnant women in first trimester in Private Practice Midwives BPM Ni Wayan Suri in Denpasar City.